OPTIMASI SISTEM PROSES PRODUKSI BIODIESEL DARI MINYAK JELANTAH DAN METANOL DENGAN KATALISATOR ABU TANDAN KOSONG SAWIT DAN UJI UNJUK KERJANYA PADA MESIN DIESE - , Muhammad Imaduddin, S.Si, Ir. Supranto, M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Research on the production of biodiesel from used frying oil and methanol with catalyst EFB ash has been done. The purpose of this study is to find the optimization of biodiesel production process that the parameters consisting of temperature, time, and percentage weight of catalyst so it can be determined the optimal conditions of production processes, appropriate based on SNI standards, and known its performance in diesel engines. The study begins with an analysis of potassium in the EFB ash using AAS and composition analysis of used cooking oil in the form methyl esters (biodiesel) using GC-MS. EFB ash extracted in methanol used as catalysts in the transesterification reaction. Characterizing the physical properties of biodiesel using ASTM standard methods and test its performance in diesel engines using diesel PETTER. The results showed that the metal content of potassium in the ash of EFB is 14.75 % ash weight. The main component of biodiesel from used frying oil are methyl palmitate and methyl oleate. The optimal conditions of biodiesel production process were achieved at temperature 60 Â°C, reaction time 60 minutes, and weight percentage of catalyst is 8 % oil weight. The character of the physical properties of biodiesel at optimal condition relatively accord with the specification standard of SNI 04-7182-2006. At its performance test on diesel engine using fuel of B0, B20, and B40 was known that at various engine speed with the same power, SFC value of B40 is the highest, while the SFC of B0 and B20 have a thin distinction. At different power, SFC value of B40 is also relatively higher compared with B0.